Land purchasing behavior of real estate enterprises: An organizational status perspective - Liu, Guangping; Cui, Yuhui; Li, Ze (International Journal of Strategic Property Management, 2025)
Based on resource dependency and signaling theories, this study examines how organizational status affects land purchasing behavior in listed real estate enterprises on China’s Shanghai and Shenzhen A-shares from 2006 to 2023. The findings indicate that the organizational status of real estate enterprises positively impacts their land purchase area, price, and quantity. Further analysis reveals that managerial overconfidence mediates this relationship. Heterogeneity analysis shows that the organizational status of state-owned real estate enterprises positively influences all three types of land purchasing behaviors, while for non-state-owned enterprises, it only significantly affects the area and price of land purchases, not the quantity. This study enriches the theory on land purchasing behavior of real estate enterprises, expands the application scope of organizational status, reveals the mechanisms through which organizational status affects land purchasing behavior and provides valuable insights for guiding rational competition among real estate enterprises, optimizing land resource utilization, and promoting the healthy and sustainable development of the real estate industry.